Tax Aggressiveness Affected by Corporate Social Responsiblity, Earnings Management, and Audit Quality - Noveryan Irfansyah; Icuk Rangga Bawono; Irianing Suparlinah (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
This study aims to examine whether tax aggressiveness can be affected by corporate social responsibility, earnings management and audit quality. This study uses manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018 as research objects with a total of 165 companies. In determining the sample in this study using a purposive sampling method, and obtained a total sample of 46 companies and a study period of 3 years so that the sample size becomes 138 data units. The results of this study indicate that tax aggressiveness can not be affected by corporate social responsibility, tax aggressiveness can be affected positively and significantly by earnings management and tax aggressiveness can be affected negatively and significantly by audit quality.